Community HIV‐1 drug resistance is associated with transmitted drug resistance. Issue 6 (12th January 2014) - Tilghman, MW; Pérez‐Santiago, J; Osorio, G; Little, SJ; Richman, DD; Mathews, WC; Haubrich, RH; Smith, DM
<x xml:space="preserve">Abstract</x> Objectives As community viral load (CVL) measurements are associated with the incidence of new HIV‐1 infections in a population, we hypothesized that similarly measured community drug resistance (CDR) could predict the prevalence of transmitted drug resistance (TDR). Methods Between 2001 and 2011, the prevalences of HIV‐1 drug resistance for patients with established infection receiving HIV care (i.e. CDR) and TDR in recently infected patients were determined in San Diego. At each position in HIV‐1 reverse transcriptase (RT) and protease (pro), drug resistance was evaluated both as the overall prevalence of resistance‐associated mutations and by weighting each resistance position to the concurrent viral load of the patient and its proportion to the total viral load of the clinic (CVL). The weighting was the proportion of the CVL associated with patients identified with resistance at each residue. Spearman ranked correlation coefficients were used to determine associations between CDR and TDR. Results We analysed 1088 resistance tests for 971 clinic patients and baseline resistance tests for 542 recently infected patients. CDR at positions 30, 46, and 88 in pro was associated with TDR between 2001 and 2011. When CDR was weighted by the viral load of patients, CDR was associated with TDR at position 103 in RT. Each of these associations was corroborated at least once using shorter measurement intervals. Conclusions Despite evaluation of a limited percentage of chronically infected patients in San Diego, CDR correlated with TDR at key resistance positions and therefore may be a useful tool with which to predict the prevalence of TDR.